Eunike Celine Siregar Reconciliation of Mining Planning and Realization at Pit 4 Pt Adimitra Baratama Nusantara Subcontractor - eunike, Eunike Celine Siregar; windhu, Windhu Nugroho; tommy, Tommy Trides (Journal of World Science, 2022)
PT. RPP Contractors Indonesia implements open-pit mining with open pit mining methods. Which has a coal mining production target in June 2021 of 111,800 tons of coal and overburden stripping of 1,596,278 BCM. However, mining realization often experiences discrepancies every month, therefore research is needed to analyze the differences in mining planning and realization, the factors that cause differences, and efforts that can be made to minimize the mismatch of mining planning to the realization of mining. Reconciliation is finding a way to create two different ideas, facts, etc. The research method conducted is to match the mining planning in June 2021 with the actual mining in June 2021 to get the percentage of the mining match. From the results of the study, it is known that in June 2021 the achievement of mining according to planning is 111,800 tons of coal and 1,596,278 BCM overburden. And from observations, the causes of the difference between planning and realization in the field are the number of inappropriate fleets, the productivity of unsuitable tools, and less than optimal representation. Therefore, efforts are needed to minimize these discrepancies by increasing effective working time and increasing supervision.